Large‐scale mapping of anthropogenic relief features—legacies of past forest use in two historical charcoal production areas in Germany. Issue 4 (7th January 2020) - Schneider, A.; Bonhage, A.; Raab, A.; Hirsch, F.; Raab, T.
Abstract: With the increasing availability of high‐resolution digital elevation models (DEMs), large‐scale mapping of anthropogenic relief features has become feasible for more areas. However, the landscape‐scale distribution patterns of anthropogenic landforms and the quality of DEM‐based mapping can be highly heterogeneous. In this study, we mapped relict charcoal hearths (RCHs) in two study regions with differing environmental backgrounds, covering forest areas of more than 15, 000 km 2, analyzed the RCH distributions and evaluated possibilities for predictive modeling of RCH occurrence with respect to natural and cultural landscape structures. More than 45, 000 RCHs were recorded in each region, with high site densities even in areas remote from charcoal‐consuming industries. Variations in the quality of DEM‐based mapping were related to small‐scale differences in the DEM quality and larger‐scale substrate heterogeneity. A clear association between RCHs and historical industrial sites was found in the Northern European Lowland; while the density of mapped RCHs was predominantly related to geology and morphology in the lower mountain ranges. The results show that variations in mapping quality across scales and the natural and cultural background of a region need to be considered so that the mapping of anthropogenic relief features can contribute to an improved understanding of land‐use history.